Obuntu-bulamu and the Law: an extra textual aid statutory interpretation tool - Lubogo, Isaac Christopher (Marianum Press Ltd, 2020)
There is a patriotic obligation on all of us not to allow our Constitution and the idea of respect for human rights and dignity to slide into such disrepute.The debate over whether or not Obuntu-bulamu can be translated into a justiciable principle turns not only on the definition one gives to Obuntu-bulamu, but also on how and why Obuntu-bulamu can be considered an ’African’ value. Obuntu-bulamu, or something very close to it, appears in most African languages what remains therefore is the complex ethno-philosophical questions of whether or not Obuntu-bulamu actually represents a key ethical principle or ideal in African philosophy generally. In doing so one should be able to realise, at the very least, that the question of ’what is’ and ’what can’ constitute an ’African’ legal philosophy lies at the very heart of this discussion. A related question therefore becomes what role should this African philosophy, including African political and ethical philosophy; play in the development of a constitutional jurisprudence for Uganda.In this book, I construct an ethical principle that not only grows out of indigenous understandings of Obuntu-bulamu, but is fairly precise and clearly accounts for the importance of individual liberty, and is readily applicable to addressing present-day Uganda as well as other societies. To flesh out these claims, I explain how the Obuntu-bulamu-based moral theory I spell out how it serves as a promising foundation for human rights. Although the word Obuntu-bulamu does not feature explicitly in most Constitutions that were ultimately adopted in some countries, my claim is that a philosophical interpretation of values commonly associated with Obuntu-bulamu can entail and plausibly explain this book construal of human rights. In short, I aim to make good on the assertion made by sound Constitutional jurisprudence that Obuntu-bulamu is the ‘underlying motive of the Bills of Rights.Note that this is a work of jurisprudence, and specifically of normative philosophy, and hence that I do not engage in related but distinct projects that some readers might expect. For one, I am not out to describe the way of life of any particular people. Of course, to make the label Obuntu-bulamu appropriate for the moral theory I construct, it should be informed by pre-colonial African beliefs and practices (since reference to them is part of the sense of the word as used by people in my and the reader’s linguistic community). However, aiming to create an applicable ideal that has an African pedigree and grounds human rights, my ultimate goal in this book is distinct from the empirical viiproject of trying to accurately reflect what a given traditional black people believed about morality something an anthropologist would do. For another, I do not therefore engage in legal analysis, even though I do address some texts prominent in African legal discourse. My goal is not to provide an interpretation of caselaw, but rather to provide a moral theory that a jurist could use to interpret caselaw, among other things.I begin by summarizing the Obuntu-bulamu-based moral theory that is developed elsewhere and then articulate its companion conception of human dignity. Next, I invoke this concept of human dignity to account for the nature and value of human rights of the sort characteristic required as a sound Ugandan constitution. I apply the moral theory to some human rights controversies presently facing Uganda (and other countries as well), specifically those regarding suitable approaches to dealing with compensation for claims, and sound policies governing the use of deadly force by the government. My aim is not to present conclusive ways to resolve these contentious disputes, but rather to illustrate how the main objections to grounding a public morality on Obuntu-bulamu, regarding vagueness, collectivism and anachronism, have been rebutted, something I highlight in the conclusion.As with any other system, the Obuntu-bulamu philosophy and the African socio-cultural framework present some challenges. Most of the challenges that are reviewed are based on my experience and my own observation as part of the African community. The findings of others who have researched this and related questions are also referred to accordingly.
Keywords: Obuntu-bulamu (Luganda) - Legal aspects; Law -Jurisprudence; Obuntu-bulamu (Luganda) - Ethno-philosophical aspects